2017
DOI: 10.4103/0366-6999.217093
|View full text |Cite
|
Sign up to set email alerts
|

How to Fill the Cavity after Curettage of Giant Cell Tumors around the Knee? A Multicenter Analysis

Abstract: Background:Intralesional excision with curettage is the standard method of giant cell tumor (GCT) treatment, but the ideal filling material after curettage remains controversial. The purpose of this study was to compare the oncological and functional outcomes which underwent cementation or bone grafting after GCT curettage around the knee.Methods:We reported 136 cases with GCTs in distal femur or proximal tibia who accepted curettage from five clinical centers during the last 15 years. All patients were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…This method is simple and practical with satisfactory clinical effects 42 . The immediate stability of a tumor cavity filled with bone cement contributes to the early recovery of limb function, but bone cement filling adjacent to the articular surface may lead to painless arthritis 71 . In addition, compared with the dynamic process of bone graft reconstruction, the relatively static environment after bone cement filling is more conducive to postoperative imaging follow-up observation 71,72 .…”
Section: Recommendation 12: Microwave Ablation Of Skip Metastasis In mentioning
confidence: 99%
“…This method is simple and practical with satisfactory clinical effects 42 . The immediate stability of a tumor cavity filled with bone cement contributes to the early recovery of limb function, but bone cement filling adjacent to the articular surface may lead to painless arthritis 71 . In addition, compared with the dynamic process of bone graft reconstruction, the relatively static environment after bone cement filling is more conducive to postoperative imaging follow-up observation 71,72 .…”
Section: Recommendation 12: Microwave Ablation Of Skip Metastasis In mentioning
confidence: 99%
“…This cement could be replaced with bone after one or two years if the GCBT shows no recurrence. In addition, chemically toxic substances (e.g., alcohol or phenol) are often added to kill the remaining GCBT cells [45].…”
Section: Curettagementioning
confidence: 99%
“…[ 8 , 9 ] This type of surgical procedure commonly includes the use of physical or surgical adjuvants following intralesional curettage, such as the employment of high-speed burring and pulse lavage to improve the effectiveness of curettage and extend the surgical margins, filling with PMMA, and the use of chemicals (hydrogen peroxide, phenol, and alcohol), resulting in a relatively low local recurrence of 0% to 12% and disease-free survival rates as high as 85%. [ 2 , 4 , 9 11 ] Several published medical studies have reported that extensive intralesional curettage and the application of PMMA is recommended for primary and recurrent giant-cell tumors and has the advantages of easier use, cytotoxic effects, necrotic effects on remaining tumor remnants, early detection of local recurrences at follow-up, immediate full weight bearing after surgery and stabilization of the affected joint. [ 12 , 13 ] However, despite these advantages, some scholars are concerned that the application of PMMA directly adjacent to a chondral surface, which is associated with an increased risk of thermal damage to the underlying cancellous and subchondral bone, may increase the healing time in local bone tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 , 13 ] However, despite these advantages, some scholars are concerned that the application of PMMA directly adjacent to a chondral surface, which is associated with an increased risk of thermal damage to the underlying cancellous and subchondral bone, may increase the healing time in local bone tissues. [ 1 , 11 , 14 , 15 ] Additionally, the special mechanical properties of cement may affect the underlying articular cartilage and contribute to nononcologic complications, including degenerative changes in the adjacent joint and fracture. [ 11 , 16 18 ] In a multicenter retrospective Chinese primary bone tumor study, 136 patients with GCTB in the distal femur or proximal tibia were followed for an average of 86 months.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation